Analysis of root mycorrhizal colonization and soil GRSP of Osmanthus fragrans (Current Horticulture, 2024)
The experiment was conducted to analyze the status of root colonization by arbuscular mycorrhizal (AM) fungi and soil glomalin-related soil protein (GRSP) in plant of Osmanthus fragrans (YinGui) in the field. Three treatments, 1.0 m (S1.0m), 1.4 m (S1.4m) and 1.8 m (S1.8m) away from the trunk of plants of O. fragrans were designed. The results showed that plants were AM plants, as observed the AM structure. The AM colonization varied from 10.2% to 21.2% in field and greater mycorrhizal colonization was found in S1.4m. Easily extractable GRSP (EE GRSP) ranged from 0.457 to 0.565 mg/g soil and was higher in S1.4m than in S1.0m and S1.8m. No any significant difference was observed in difficultly extractable GRSP (DE-GRSP) and total GRSP. A greatly significantly positive correlation was found between AM colonization and EE-GRSP.
Keywords: Arbuscular mycorrhiza; EE-GRSP; Glomalin; Mycorrhizal colonization; Osmanthus fragrans